Association between Migrant Women’s Legal Status and Prenatal Care Utilization in the PreCARE Cohort - Eslier, Maxime (Int J Environ Res Public Health, 2020)
Barriers to access to prenatal care may partially explain the higher risk of adverse pregnancy outcomes among migrants compared with native-born women in Europe. Our aim was to assess the association between women’s legal status and inadequate prenatal care utilization (PCU) in France, where access to healthcare is supposed to be universal. The study population was extracted from the PreCARE prospective cohort (N = 10,419). The associations between women’s legal status and a composite outcome variable of inadequate PCU were assessed with multivariate logistic regressions. The proportion of women born in sub-Saharan Africa (SSA) was higher among the undocumented than that of other migrants. All groups of migrant women had a higher risk of inadequate PCU (31.6% for legal migrants with European nationalities, 40.3% for other legal migrants, and 52.0% for undocumented migrants) than French-born women (26.4%). The adjusted odds ratio (aOR) for inadequate PCU for undocumented migrants compared with that for French-born women was 2.58 (95% confidence interval 2.16–3.07) overall, and this association was similar for migrant women born in SSA (aOR 2.95, 2.28–3.82) and those born elsewhere (aOR 2.37, 1.89–2.97). Regardless of the maternal place of birth, undocumented migrant status is associated with a higher risk of inadequate PCU.